As placas votivas (e o báculo) da Lapa da Galinha, na primeira metade do 3.º milénio a.n.e. - Gonçalves, Victor S. (2018)
Lapa da Galinha (literally “The chicken’s cave”) is a typical small cave of the portuguese Estremadura. Located near Alcanena, it was excavated more than a century ago and, at the time, the numerous human remains therein identified have been removed to the local cemetery and are not available for study and dating. A first note about this cave, very insufficient for the importance of the site, have been presented to the 1st National Congress of Archaeology. Lapa da Galinha revealed, for the cultural milieu in which it is included, a relatevely considerable amount of engraved schist plaques and a rather peculiar “cross”, in which some have seen a figuration of an axe. If the “cross” is so peculiar and unique, the plaques form a very bizarre but simple ensemble. Most of them are double faced (in Portuguese: placas bipolares). The motifs and decorative patterns are also peculiar and some present unusual shapes for the area of Estremadura, disclosing possible cultural influences of other regional areas. The PLACA NOSTRA Project shows, for the first time, drawings of all the available plaques and presents some new perspectives on the meaning of the “Lapa da Galinha connection”.